Collaboration among teachers in inclusive special education program classrooms - Ab. Latiff, Maizatul Azmah; Wan Mohamed, Wan Azlinda; Mohd Azrani, A. (American Scientific Publishers, 2017)
Collaboration between teachers and special education teachers is a vital factor in ensuring the success of the implementation of the Inclusive Education Programs especially in the teaching and learning aspects. Until 2016, there is no detailed document or information regarding how the collaboration is conducted or implemented in the inclusive classrooms. Therefore, this study is aimed to explore how collaboration is conducted and implemented in the Inclusive Special Education Program classrooms, particularly identifying the stage of collaboration the school are at and approach used in the inclusive classrooms. To achieve this, a survey questionnaire was used as an instrument for this study and it is conducted on 53 schools and 441 participants including headmasters, senior assistant principals for special education teachers, subject teachers and special education teacher. Results showed that most of the participants are at the “Starting a partnership” stage (mean score = 4.165, SD = 0.797). The type of collaboration approach that are usually being used is the “collaboration-consultation” approach (mean score = 4.10, SD = 0.721). This suggests that more action is needed to ensure the successful implementation of an inclusive program. This is because without done the recommended steps of collaboration, the inclusive may not carried out effectively. A successful inclusive classroom also can be achieved through multiple approaches of collaboration are implemented. Therefore, knowledge about steps and approaches of collaboration should be knowledgeable to general, special education teacher and also school administrators.